P4.143 The Relationship Between Emotional Intelligence and Mental Health with HIV-Related High Risk Behaviours Among Female Sex Workers in Shiraz - Iran. (13th July 2013) - Lari, M Amini; Bagheri, P; Ameli, F
Abstract : Background: Psychological problems have significant associations with HIV-related high-risk behaviours among female sex workers (FSW). The present study aimed to investigate emotional intelligence and mental health and their relationships with high-risk behaviours among FSW in Shiraz, Iran. Methods: This cross-sectional study, conducted from October 2011 to May 2012, was based on a convenience sampling method used to recruit 125 FSW and 125 control women. After providing informed consent, each woman completed validated questionnaires (SCL-90-R, Bar-On Emotional Quotient [EQ] Inventory and high-risk behaviours). Results: In comparison to the control group, the mean age at first sexual relationship was lower among sex workers, and most of them (80.4%) had not used condoms in their most recent sexual intercourse. FSW showed lower EQ scores and more psychological symptoms in all dimensions (P < 0.003). A significant inverse relationship was found between global severity indexes (GSR) scores and use of a condom in the most recent sexual intercourse. According to EQ scores, significant relationships were observed for interpersonal skills and stress management with the number of sexual partners during the previous week and condom use in the most recent sexual intercourse (P < 0.05). Discussion: Considering the relationship of high-risk behaviours with lower emotional intelligence and mental health among FSW, psychological interventions are needed in order to prevent high-risk behaviours and HIV transmission.